2022
DOI: 10.3390/land11060867
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Change and Ecosystem Health Assessment on Shanghai–Hangzhou Bay, Eastern China

Abstract: Reasonable quantitative assessment on urban ecosystem health is conducive to the sustainable development of the economy and human society. This paper quantitatively evaluated the impact of land use change on ecosystem services and ecosystem health by building a comprehensive evaluation system (vigor–organization–resilience–ecosystem services), and then analyzed the spatial-temporal pattern, evolution characteristics, and driving factors in the Shanghai–Hangzhou Bay area (SHB) over the 2000–2015 period. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…This finding suggests that areas of high value ecosystem services are mainly located in the peripheries of cities. This is similar to the results of other studies that found the greatest decline in habitat quality in downtown areas [38] and found that the urban ecosystem health significantly deteriorated [19]. Changes in the ESV are a direct reflection of land use changes, and in the context of rapid urbanization, dramatic land use changes have become a major factor in weakening and destroying the value of urban ecosystem services [52].…”
Section: Change In Land Use and Ecosystem Servicessupporting
confidence: 88%
See 1 more Smart Citation
“…This finding suggests that areas of high value ecosystem services are mainly located in the peripheries of cities. This is similar to the results of other studies that found the greatest decline in habitat quality in downtown areas [38] and found that the urban ecosystem health significantly deteriorated [19]. Changes in the ESV are a direct reflection of land use changes, and in the context of rapid urbanization, dramatic land use changes have become a major factor in weakening and destroying the value of urban ecosystem services [52].…”
Section: Change In Land Use and Ecosystem Servicessupporting
confidence: 88%
“…The development of spatial information technology, such as remote sensing, has further pushed forward research on ecosystem services, and the evaluation method of coupling land use changes and ecosystem service value (ESV) has been widely used [13][14][15]. Several studies have examined the effects of land use changes on the value of services of different ecosystems, such as studies on highlands [16], coastal areas [17][18][19], and urban landscapes [17,[20][21][22][23]. At present, an increasing number of scholars at home and abroad are studying the impact of land use changes on ESV, and ecosystem service valuation methods are widely used in urban planning.…”
Section: Introductionmentioning
confidence: 99%
“…Land use intensity also influenced the ecological integrity condition of different ecosystem types, such as wetland (Jiang et al, 2015) and island zones (Jiang et al, 2018). However, compared with desert ecosystems, the explanatory power of land use intensity in other ecosystems was much weaker, and economic factors had more weight in terms of affecting ecosystem integrity (Xiao et al, 2022;Xu et al, 2022). Typically, the economy has a complicated influence on the local natural ecological environment (Kijima et al, 2010), while our study showed that the economic factor had a lower influence on ecological integrity.…”
Section: Driving Factors Of Ecological Integritymentioning
confidence: 99%
“…(68,69) Hangzhou Bay is an important part of the Yangtze River Delta owing to its geographical location, dense population, concentrated cities, and developed industry. (70,71) Since China's reform and opening up, the Hangzhou Bay area has witnessed rapid social and economic developments. It is one of the fastest growing regions in China and has brought together a large number of people and economic activities.…”
Section: Study Areamentioning
confidence: 99%